2015
DOI: 10.1093/ijpor/edv037
|View full text |Cite
|
Sign up to set email alerts
|

Partisanship, Information, and Perceptions of Government Corruption

Abstract: This article analyzes how partisanship and political information influence perceptions of government corruption at national and regional levels and whether information attenuates the impact of partisanship. The data are drawn from surveys of recent elections held in Canada, France, Germany, Spain, and Switzerland. Almost everywhere, partisans of the incumbent parties and the most-informed citizens perceive less corruption than their nonpartisan and less-informed counterparts. However, there is no evidence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…Information is available on the dedicated website: http://electoraldemocracy.com/. For a scientific exploitation of the survey, seeBlais et al (2015).16 The MEDW dataset also contains information about Spain. We could however not use it, because the question on perceived corruption of municipalities was asked to a too small fraction of respondents.…”
mentioning
confidence: 99%
“…Information is available on the dedicated website: http://electoraldemocracy.com/. For a scientific exploitation of the survey, seeBlais et al (2015).16 The MEDW dataset also contains information about Spain. We could however not use it, because the question on perceived corruption of municipalities was asked to a too small fraction of respondents.…”
mentioning
confidence: 99%
“…High-income and highly educated citizens tend to perceive lower levels of corruption compared with other citizens (p. 5). Blais et al (2015) also come to the conclusion in most of their cases that the better informed citizens perceive less corruption than less informed ones. Hence, we expect that the general public diverges considerably from groups with an information advantage in its perceptions of corruption; and we expect the groups to diverge in two ways in less corrupt countries:…”
Section: Stjórnmál and Stjórnsýslamentioning
confidence: 89%
“…The empirical literature shows that partisans tend to latch on to positive news about their favored party, while selectively filtering out or rejecting negative information (Jerit and Barabas 2012). With respect to corruption specifically, several studies have found that partisan supporters of the sitting government perceive lower corruption on average compared with opposition voters or non-partisans (Anderson and Tverdova 2003;Blais et al 2017;Agerberg 2020), or that they tend to be willing to overlook corruption scandals in their own party in elections (Anduiza et al 2013; Charron and Bågenholm 2016).…”
Section: Effect 2: Media Source and Polarization Of Institutional Assmentioning
confidence: 99%